Dropout Voices of Urlabari Multiple Campus (UMC): A Phenomenological Study - Magar, Bishnu; Gautam, Ambika (New Journey, 2025)
This paper deals with the causes of drop out case of Urlabari Multiple Campus (UMC) analyzing drop out students of two consecutive years -2075/76 BS and 2076/77 BS (2018/19 & 2019/20 AD). The purpose of the study is to explore the participants lived experiences regarding their drop out behavior. There has been a national circumstance that the students’ retention in the campus level is almost degrading and thus this study is relevant to describe why students from UMC drop their study. It is a phenomenological study which analyses the lived experiences of the research participants drawing information through Seidman’s three stages of interviews dealt with in- depth interviews of six participants. The constructivist paradigm was maintained in order to comprehend the methodology of phenomenology establishing trustworthiness through multiple realities ontologically and epistemologically. There were several causes of campus dropout including marriage, scholarship negligence, foreign job placement, internal job placement, poverty, lack of parental guidance and the like. The lived experiences are interwoven with the causes of the dropout and discussed vibrantly.